Exploratory study of the dispensing patterns of vaccines by a sample of community pharmacies in Southern Africa - Ilse Truter (Taylor & Francis Group, 2018)
Introduction: Vaccination is one of the most cost-effective healthcare interventions. Pharmacies in South Africa provide a vaccination service where childhood immunizations, some travel vaccines and vaccines for specific populations are dispensed and administered, but little has been published on which vaccines are dispensed and at what cost. Areas covered: This retrospective drug utilization study determined the dispensing patterns of vaccines in community pharmacies during 2015 with the focus on the types and cost of vaccines dispensed in ATC group J07. Expert commentary: Of the 140 902 vaccines dispensed to 79 415 patients, viral vaccines (J07B) accounted for most of the prescriptions (82.7% of volume; 62.3% of cost), followed by bacterial vaccines (J07A) (17.1% of volume; 37.5% of cost), and bacterial and viral vaccines combined (0.2% of volume; 0.3% of cost). There was an increase in the dispensing patterns of viral vaccines (J07B) in the period just before the winter months. Half of all vaccines (50.4%) were for the influenza vaccine (J07BB01). This vaccine accounted for only 15.6% of the total cost of vaccines. The most expensive vaccines were pneumococcal polysaccharide conjugate vaccine (13-valent adsorbed, pre-filled syringe) (J07AL01), followed by human papillomavirus bivalent vaccine (J07BM02).